Quality protein maize for small scale farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Improved maize with double the nutritional qualities of standard varieties is beginning to spread to small-scale farmers in many parts of Africa. Known as QPM or Quality Protein Maize, it has double the levels of lysine a particularly important...